Adaptation of smallholder maize farmers to temperature and rainfall variability in Capricorn District Municipality, Limpopo Province, South Africa - Mazwi, Kabelo Makadikwe (My University, 2019)
Refer to document
Thesis (M. Sc.) -- University of LImpopo, 2019
Keywords: Climate change; Smallholder maize farmers; Rainfall; Capricorn and District municipality; Climatic changes -- Law and legislation; Climatic changes -- Risk management